Supplementation of yam bean (Pachyrhizus erosus L.) fiber ameliorates dyslipidemia, liver pathology and hypersecretion of metabolic hormones in mice fed a highfat diet - Putra Santoso; Rita Maliza (Journal of HerbMed Pharmacology, 2024)
Introduction: Yam bean (Pachyrhizus erosus L.) offers numerous health benefits. However, the effects of its dietary fiber (yam bean fiber, YBF) on dyslipidemia, liver disease, and the overproduction of metabolic hormones, specifically glucagon-like peptide-1 (GLP1) and fibroblast growth factor 21 (FGF21), resulting from a high-fat diet (HFD) remain underexplored. Thus, our present investigation sought to address this gap. Methods: Adult male mice (n = 24) were randomly assigned into four different groups such as normal diet (ND) as a control group, HFD, and HFD supplemented with either 2.5% or 10% YBF. After a 12-week dietary regimen, plasma lipid profiles, liver histology and biochemistry, and the levels of FGF21 and GLP-1 were assessed. Results: YBF supplementation, especially at 10% dose, effectively lowered total serum cholesterol, triglyceride (TG), and low-density lipoprotein (LDL) compared with those fed HFD (P < 0.05). YBF also reduced liver weight and mitigated the elevation of malondialdehyde (MDA) and the depletion of catalase (CAT) activity induced by HFD in liver tissues (P < 0.05). Furthermore, 10% YBF supplementation effectively countered liver pathology, including central vein enlargement, hepatic steatosis, inflammation, abnormal sinusoids, and hepatocyte degeneration caused by HFD (P < 0.05). YBF at 10% also attenuated the HFDinduced hypersecretion of FGF21 and GLP-1 hormones. Conclusion: Our findings indicate that YBF supplementation could counteract the adverse effects of HFD, particularly in terms of dyslipidemia, liver disease, and metabolic hormone imbalances. Incorporating YBF into diets may thus offer protective benefits against HFDinduced metabolic diseases and associated health issues.